1986
DOI: 10.1002/anie.198610971
|View full text |Cite
|
Sign up to set email alerts
|

13C‐ENDOR Investigation of an Organic Tetraradical in the Quintet State; Synthesis of a Fourfold 13C‐Labeled Tetrakisgalvinol

Abstract: elution with 5 mM sodium phosphate buffer on a phosphate-containing Dowex 1-X2 column. The free trisaccharide 3, whose interglycosidic linkages were confirmed by i H-NMR spectroscopy,"] was thereby obtained directly on a 50-pmol scale (yield: 31 mg, 52%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 11 publications
1
29
0
Order By: Relevance
“…Through Fourier transform infrared (FTIR) spectroscopy and elemental analysis, they found that the monomers were almost completely converted to polymers under reaction conditions of 400 °C and 40 h . A novel three‐dimensional porous aromatic framework based on tetrakis(4‐cyanophenyl)methane building unit and a triangular triazine ring was designed and produced, showing selective sorption of benzene, thermal stability and a Langmuir surface area of 1109 m 2 g −1 . Wang and co‐workers reported ultra‐microporous polymers based on one of the most common thermosetting networks, cyanate ester resins, in facile cyano cyclotrimerization .…”
Section: Preparation Routes To Cmpsmentioning
confidence: 99%
“…Through Fourier transform infrared (FTIR) spectroscopy and elemental analysis, they found that the monomers were almost completely converted to polymers under reaction conditions of 400 °C and 40 h . A novel three‐dimensional porous aromatic framework based on tetrakis(4‐cyanophenyl)methane building unit and a triangular triazine ring was designed and produced, showing selective sorption of benzene, thermal stability and a Langmuir surface area of 1109 m 2 g −1 . Wang and co‐workers reported ultra‐microporous polymers based on one of the most common thermosetting networks, cyanate ester resins, in facile cyano cyclotrimerization .…”
Section: Preparation Routes To Cmpsmentioning
confidence: 99%
“…Anhydrous zinc chloride was further dried at 120 C in vacuo overnight prior to use. Tetra(4-bromophenyl)methane [15] and tetra(4-bromophenyl)ethene [16] were synthesized according to reported procedures.…”
Section: Methodsmentioning
confidence: 99%
“…BPM (127 mg, 0.2 mmol) and PBPM (246 mg, 0.15 mmol), which were prepared following literature methods (Supporting Information), 13,14 were dissolved in anhydrous DMF (10 mL) under an argon atmosphere. Cesium carbonate (326 mg, 1.0 mmol), tetrakis(triphenylphosphine)palladium(0) (23.0 mg, 0.02 mmol), water (2.0 mL), and ethanol (2.0 mL) were added to the solution subsequently.…”
Section: Methodsmentioning
confidence: 99%